Mobilizing Archaeologists: Increasing the Quantity and Quality of Data Collected in the Field with Mobile Technology. Issue 1 (February 2014) - Austin, Anne
Abstract: Data collection takes up much of the already limited time archaeologists have to excavate and often requires additional time to digitize. Moreover, despite efforts to standardize data, archaeologists often find errors such as blank or incorrectly recorded fields. To avoid these issues, several projects have made use of tablet computers to streamline and digitize data, but this process can be opaque, specialized, and expensive. Previous research has addressed neither the general feasibility of developing and utilizing mobile devices for data collection nor the quality and quantity of these data. In this article, I review existing methods and practices for integrating data collection on mobile devices in order to evaluate the costs and feasibility of transitioning to a mobile-based data collection system. Through a case study using OsteoSurvey, a series of bioarchaeological data collection forms for Android tablets, I assess the efficacy of data collection on mobile devices. An experiment comparing OsteoSurvey to traditional paper forms demonstrates that participants saved time and made fewer mistakes using the OsteoSurvey forms, resulting in the collection of 21–32 percent more data. Consequently, data collection with mobile devices can significantly increase the overall productivity and quality of archaeological research